pEVL: A Linear Plasmid for Generating mRNA IVT Templates With Extended Encoded Poly(A) Sequences - Alexandra E Grier; Stephen Burleigh; Jaya Sahni; Courtnee A Clough; Victoire Cardot; Dongwook C Choe; Michelle C Krutein; David J Rawlings; Michael C Jensen; Andrew M Scharenberg; Kyle Jacoby (Elsevier, 2016)
Increasing demand for large-scale synthesis of in vitro transcribed (IVT) mRNA is being driven by the increasing use of mRNA for transient gene expression in cell engineering and therapeutic applications. An important determinant of IVT mRNA potency is the 3' polyadenosine (poly(A)) tail, the length of which correlates with translational efficiency. However, present methods for generation of IVT mRNA rely on templates derived from circular plasmids or PCR products, in which homopolymeric tracts are unstable, thus limiting encoded poly(A) tail lengths to ≃120 base pairs (bp). Here, we have developed a novel method for generation of extended poly(A) tracts using a previously described linear plasmid system, pJazz. We find that linear plasmids can successfully propagate poly(A) tracts up to ≃500 bp in length for IVT mRNA production. We then modified pJazz by removing extraneous restriction sites, adding a T7 promoter sequence upstream from an extended multiple cloning site, and adding a unique type-IIS restriction site downstream from the encoded poly(A) tract to facilitate generation of IVT mRNA with precisely defined encoded poly(A) tracts and 3' termini. The resulting plasmid, designated pEVL, can be used to generate IVT mRNA with consistent defined lengths and terminal residue(s).